Uji aktivitas penyembuhan luka sayat menggunakan sediaan patch ektrak etanol daun jambu biji (psidium guajava l.) secara in vivo - Mulyadi Dai Muhammad Hafidz; Lina Rahmawati Rizkulloh; Ali Nofriyaldi (Jurnal Farmasi & Sains Indonesia, 2025)
The ethanol extract of (Psidium guajava L.) leaves, containing key phytocmhemicals such as tannins, flavonoids, and saponins, has demonstrated potential in enhancing wound repair. This research aimed to formulate a transdermal patch and investigate its in vivo wound-healing activity. Extraction was carried out through maceration of the simplicia using 96% ethanol as the solvent. Patches were formulated with HPMC and PVP, containing 2.5%, 5%, and 10% extract (F1, F2, F3). Physical evaluation (homogeneity, pH, thickness, adhesion) was performed. Rabbits (n=5) with a 2 cm dorsal incision were treated daily with patches (F1-F3), A negative control was represented by a (patch without extract) while the positive control used (povidone-iodine). Wound length was measured for 7 days. All evaluations met the physical requirements except pH at (F2: 6,6±0,1; F3: 6,8±0,1). F3 (10% extract) showed the highest wound healing activity, reducing wound length to 2 mm on day 7, significantly better than the control (7 mm) and lower concentrations (F1: 4 mm; F2: 3 mm). Guava leaf extract patches were effective at healing incised wounds, with concentration-dependent efficacy.